2017
DOI: 10.1189/jlb.3ma0117-020r
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 potentiates the activation of neutrophils by the etiological agent of gout, monosodium urate crystals

Abstract: Gout is one of the most painful types of arthritis that arises when the body mounts an acute inflammatory reaction against a crystallized form of uric acid known as monosodium urate crystals (MSUs). Although MSUs are known to activate neutrophils, the most abundant leukocyte in the synovial fluid of patients with gout, few studies have investigated the effect on neutrophils of the simultaneous stimulation with MSU and proinflammatory mediators in the inflamed joint. Herein, we focused on a protein that is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…8-10 12 26 Also reported, MSU crystals increased both OXPHOS and glycolytic activity on human neutrophils. 27 These findings further supported the complexity of cellular metabolic programmes and responses, which varied with the type and concentration of stimuli, cell type and cell species and tissue environment. 13 28-30 For example, LPS stimulated Warburg-like metabolic reprogramming in human monocytes at concentrations between 1 and 100 ng/mL but increased OXPHOS at a low dose of 0.1 ng/ mL.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…8-10 12 26 Also reported, MSU crystals increased both OXPHOS and glycolytic activity on human neutrophils. 27 These findings further supported the complexity of cellular metabolic programmes and responses, which varied with the type and concentration of stimuli, cell type and cell species and tissue environment. 13 28-30 For example, LPS stimulated Warburg-like metabolic reprogramming in human monocytes at concentrations between 1 and 100 ng/mL but increased OXPHOS at a low dose of 0.1 ng/ mL.…”
Section: Discussionmentioning
confidence: 52%
“…14 34 Alternatively, MSU and m-CPPD crystal-induced glucose uptake might stimulate IL-1β production through Akt pathway and ROS production. 27 35 36 PI3K (phosphatidylinositol-3 kinase)/Akt pathway is commonly activated by MSU and m-CPPD crystals. 27 36 37 Akt activation enhanced IL-1β production through induction of ROS and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of the TLR‐4 ligand LPS as a major regulator of the transcriptome changes in systemic‐onset JIA neutrophils, as well as the observed strong overlap in the transcriptome of neutrophils between systemic‐onset JIA and sepsis or experimental endotoxemia, suggest that in vivo exposure to high levels of TLR‐4–stimulatory S100 proteins could explain the inflammatory gene expression in the neutrophils from patients with active systemic‐onset JIA. Indeed, several studies have demonstrated the priming of neutrophils after stimulation with S100 proteins . However, other inflammatory proteins, such as IL‐1β, might also be responsible for the primed phenotype of neutrophils in systemic‐onset JIA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mass spectrometry screening showed that S100A9 could act as an intermediate protein for Bmal1 to interact with glycolysis. Reports have pointed out that S100A9 independently induce the increase of ECAR, indicating that it can enhance the rate of glycolysis in neutrophils (Rousseau et al, 2017). The ECAR values and protein expression of glycolytic key enzymes were found to be limited after silencing S100A9.…”
Section: Discussionmentioning
confidence: 94%